Equity and poverty under rapid economic growth : the Japanese experience - Mizoguchi, Toshiyuki; Takayama, Noriyuki (Tokyo, Japan : Kinokuniya Co., 1984)
This book examines changes in the income distribution and the incidence of poverty in Japan under conditions of rapid economic growth.
Includes indexes.
Bibliography: p. 232-238.
osa;14/07/17
Loans
Keywords: Income distribution; Poor